Selenium induced selenocysteine methyltransferase gene expression and antioxidant enzyme activities in Astragalus chrysochlorus - Cakir, Ozgur; Turgut Kara, Neslihan; Ari, Sule (Acta Botanica Croatica, 2016)
Astragalus sp. are used in folk medicine because of their biological activities and are known for the ability to accumulate high levels of selenium (Se). The purpose of this study was to explore gene expression of selenocysteine methyltransferase (SMT), responsible for forming MeSeCys, and activities of ascorbate peroxidase (APX), peroxidase (POX), catalase (CAT) and glutathione reductase (GR) enzymes in callus tissues of Astragalus chrysochlorus growing in different Se-containing media. Quantitative real-time polymerase chain reaction assay was done for quantification of SMT gene transcript and it was normalized to actin gene. It was found that transcript level of callus tissues grown at 5.2 ?M and 26.4 ?M Se-enriched media was lower than that of the control callus. In contrast, a high level of Se (132.3 ?M) in the medium caused an approximately 4.26 times higher level of SMT transcript in callus than the control. APX, POX, CAT and GR enzymes were all effected by different Se concentrations. While POX and APX activities were higher then control, CAT and GR activities decreased. These results show that an increase of SMT gene expression led to a rise in APX and POX, but a suppression of CAT and GR enzymes activities in Astragalus chrysochlorus. This suggests that Se could be involved in the antioxidant metabolism in Astragalus chrysochlorus.